PENERAPAN NILAI-NILAI ETIKA KRISTEN DALAM DINAMIKA KELUARGA MODERN MENURUT KELUARAN 20:12 - Jens Yudiman; Novita Elyana, Anggun Sri Nova Kiding Allo, Grace Oktavia Pakambanan, Chindy Agustin (ADISAM PUBLISHER, 2023)
The importance of applying Christian ethical values in the dynamics of modern families is a crucial aspect that cannot be overlooked in building a foundation for a healthy and harmonious family life. Exodus 20:12 provides a clear command to honor one's parents, establishing a strong moral foundation for Christian families. However, in the ever-evolving and complex context of modern times, challenges in practicing these values may arise. Therefore, this study aims to investigate the extent to which the application of Christian ethical values, as outlined in Exodus 20:12, influences the dynamics of modern families. By understanding the practical implications of this command, it is hoped that we can provide useful guidance to Christian families in navigating the complexities of modern life while upholding Christian moral principles. This research will adopt a qualitative approach, utilizing in-depth interviews and participatory observation with a selection of Christian families who actively implement Christian ethical values in their daily lives. The data will be analyzed using a thematic approach to identify patterns and themes related to the application of Christian ethical values in family dynamics. Additionally, a questionnaire survey will be employed to gain broader insights from various family members regarding the impact and perceptions of these practices. The findings of this study indicate that the application of Christian ethical values, particularly in adhering to the command of Exodus 20:12, has a significant positive impact on the dynamics of modern families. Families who consciously practice Christian ethical values tend to have more harmonious and loving relationships among family members. Although challenges and obstacles may be encountered, the commitment to embody these values brings long-term benefits to the well-being of the family. Therefore, it is recommended that greater efforts be made to provide education and guidance to Christian families regarding the importance and methods of applying Christian ethical values in the dynamics of modern families.